[P204] Proton pencil beam scanning with motion emulated as spot shifts: Dose reconstruction for lung cancer. (August 2018) - Damkjær, Sidsel; Hoffmann, Lone; Møller, Ditte Sloth; Petersen, Jørgen Breede Baltzer; Josipovic, Mirjana; Persson, Gitte F.; Af Rosenschöld, Per Munck; Poulsen, Per
Abstract : Purpose: Respiratory motion impairs delivered dose in proton pencil beam scanning for lung cancer radiotherapy. These uncertainties can be estimated by splitting the treatment plan into phase-specific plans (based on 4DCT) and summing the dose by deformable image registration (DIR), which is labor intensive and susceptible to DIR-errors. A faster spot shift method (SSM), applicable to any motion observed during treatment, is an alternative. Methods: The SSM emulates beam's-eye-view target motion as proton spot-shifts and in-depth motion as energy changes. Dose is calculated in the end-expiration phase. The method was tested for a challenging case, with a primary 1.5 ml tumor (T) in the lower left lobe, a 4.8 ml lymph node (LN) in station 8 and large respiratory motion (T: 20 mm, LN: 6 mm). We simulated treatment delivery in end-inspiration with dose evaluation in end-expiration. A test plan had two spots hitting the center of each target in the end-inspiration. The dose in the end-expiration anatomy was estimated by warping the end-inspiration dose to the end-expiration and by calculating the dose directly in the end-expiration by the SSM using different spot shifts for T and LN. Next, a full single field plan was calculated in the end-inspiration and the dose was again estimated in the end-expiration by dose warping and SSM calculation. Target doses were compared between methods. Results: The warped dose in end-expiration represented rib and tumor doses well, while the lung entrance dose was wrong (DIR's insufficient modelling of the pleura motion). Although the SSM used a wrong entrance path through the ribs, the target doses agreed well with the original end-inspiration doses. The Dice index between warped and SSM end-expiration dose was 0.77 and 0.71 for the 50% and 95% isodoses. DVH parameters of the full plan agreed for LN, but had discrepancies for T. Conclusions: The SSM dose reconstruction agreed with the warped dose for the single spot plan. For the full plan, the agreement was good for the LN, but only fair for the T, probably due to volume changes and lung deformations near the tumor. In larger tumors with smaller motion, the SSM is likely to perform better.